2022
DOI: 10.1101/2022.02.03.478896
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plakoglobin regulates adipocyte differentiation independently of the Wnt/β-catenin signalling pathway

Abstract: The scaffold protein 14-3-3ζ is an established regulator of adipogenesis and postnatal adiposity. We and others have demonstrated that the 14-3-3ζ interactome to be diverse and dynamic, and it can be examined to identify novel regulators of physiological processes, including adipogenesis. In the present study, we sought to determine if factors that influence adipogenesis could be identified in the 14-3-3ζ interactome found in white adipose tissue of lean or obese TAP-tagged-14-3-3ζ overexpressing mice. Using m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…Through the use of CRISPR-Cas9 genome editing, we developed a useful model to explore the nuclear 14-3-3ζ interactome of APCs during adipogenesis, and this led to the discovery that 14-3-3ζ primarily acts during the early stages of adipocyte differentiation to aid in the reorganization of chromatin to allow for adipogenic gene, promoter and enhancer regions to be accessible. These findings, combined with our prior research, broaden our understanding of the importance of 14-3-3ζ in adipocyte development, metabolism, and glucose and lipid homeostasis (9, 11, 1517). Furthermore, our study clearly demonstrates for the first time that 14- 3-3ζ, a ubiquitously expressed molecular scaffold protein, has critical upstream regulatory roles in adipogenesis.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…Through the use of CRISPR-Cas9 genome editing, we developed a useful model to explore the nuclear 14-3-3ζ interactome of APCs during adipogenesis, and this led to the discovery that 14-3-3ζ primarily acts during the early stages of adipocyte differentiation to aid in the reorganization of chromatin to allow for adipogenic gene, promoter and enhancer regions to be accessible. These findings, combined with our prior research, broaden our understanding of the importance of 14-3-3ζ in adipocyte development, metabolism, and glucose and lipid homeostasis (9, 11, 1517). Furthermore, our study clearly demonstrates for the first time that 14- 3-3ζ, a ubiquitously expressed molecular scaffold protein, has critical upstream regulatory roles in adipogenesis.…”
Section: Discussionsupporting
confidence: 59%
“…In fact, we previously showed that 14-3-3ζ interacts with C/EBP-β during adipogenesis(9). As we have previously reported that mass spectrometry can be used to elucidate the 14-3-3ζ interactome under physiological and pathophysiological contexts (14, 15), we sought to define the nuclear 14-3-3ζ interactome during the differentiation of preadipocytes, with the goal of identifying novel adipogenic transcription factors or co-regulators that could be anchored by 14-3-3ζ.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations